A DUAL-STRATEGY APPROACH TO IMPROVING TAX COMPLIANCE: PENALTIES AND DRIVE-THRU SAMSAT SERVICES - Natasha Angelina Susilo; Erna Sulistyowati (RISTANSI: Riset Akuntansi, 2026)
By using quantitative methodology and SEM-PLS version 4, this study was conducted with a focus on tax sanctions and the drive thru system on Samsat to prove whether it can influence the level of tax compliance in terms of their responsibility to pay Motor Vehicle Tax at Samsat Manyar — Samsat office with the most operational scope area in Surabaya. Primary data collection through questionnaire instrument was carried out using Simple Random Sampling technique and succeeded in collecting 100 respondents. Data analyses prove that there is a significant influence between tax sanctions and Samsat Drive Thru System on taxpayer compliance. The government and Samsat can further improve service quality and be consistent on implementing regulations to increase taxpayer compliance.